Diversidade genética e respostas in vitro aos estresses hídrico e salino em Saccharum spp. - Oliveira, Leila Albuquerque Resende de (2019)
In the context of the recent search for renewable fuels that replace oil and are environmentally less harmful, sugarcane comes into focus as a product of global importance for enabling a more sustainable development. Brazil is the world's largest producer of the crop. Due the expansion of sugarcane cultivation into areas with variable climatic conditions, mainly into dry and saline regions, the use of technologies that allow the rapid identification of genotypes, with different tolerance degrees to several abiotic stresses, for exploitation in breeding programs, becomes imperative. In addition, an effective use of the genetic resources stored in germplasm banks, both to increase the genetic base and introgress traits of interest, requires prior characterization and molecular evaluation. Thus, the objective of this study was to assess the genetic diversity of Saccharum accessions in the genebank of Embrapa Coastal Tablelands (BAG Saccharum), and to characterize them in vitro for tolerance to salt and water stress, with a view to hybridizations and germplasm exchange in breeding programs. The experiments were carried out at the Laboratories of Molecular Biology and of Plant Tissue Culture, of Embrapa Coastal Tablelands. For the molecular evaluation of 26 accessions, 16 primers were used, resulting in 87 fragments with 91.13% polymorphism. The similarity of plants ranged from 0.22 to 0.87. The genetically closest plants were RB867515 and RB92579, and the most distant were PI240785 and NSL 291970. By the unweighted pair-group method based on arithmetic averages (UPGMA), four distinct groups were formed, indicating a high diversity in the BAG Saccharum. To evaluate water stress in vitro, adventitious shoots of five Saccharum robustum, S. spontaneum and S. officinarum cultivars, were cultivated in Murashige -Skoog medium, at five hydric potentials (0, -0.3, -0.6, -0.9, -1.2 MPa), induced by mannitol. Survival, shoot and root length, number of shoots and roots, bioweight, proline content in leaves and activity of antioxidant enzymes were analyzed. Differences among the sugarcane species as well as within the same species were observed under different water stress levels in vitro. Saccharum officinarum was found to be the most tolerant. Proline can be used as a biochemical indicator of response to water stress in sugarcane accessions and its accumulation was intensified in S. robustum and S. spontaneum accessions. Catalase activity remained unchanged under increased stress in the accessions evaluated. Saccharum robustum, Saccharum spp., S. officinarum, cultivated in Murashige -Skoog medium, were used at five concentrations (0, 50, 100, 150, 200 mM NaCl). Shoot and root length and number, fresh weight, dry weight, proline leaf content, total chlorophyll content and morphological alterations of the leaf tissues were analyzed. The in vitro growth of S. robustum, Saccharum spp. and S. officinarum accessions was affected by NaCl-induced salinity. Proline accumulation and chlorophyll decrease are intensified in Saccharum spp., aside from changes in the cell anatomy, characterizing the species as more salt-sensitive than the others.